2018
DOI: 10.1021/acs.jmedchem.7b01625
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Long-Lasting, Novel Bicyclic Peptide Plasma Kallikrein Inhibitors for the Treatment of Diabetic Macular Edema

Abstract: Plasma kallikrein, a member of the kallikrein-kinin system, catalyzes the release of the bioactive peptide bradykinin, which induces inflammation, vasodilation, vessel permeability, and pain. Preclinical evidence implicates the activity of plasma kallikrein in diabetic retinopathy, which is a leading cause of visual loss in patients suffering from diabetes mellitus. Employing a technology based on phage-display combined with chemical cyclization, we have identified highly selective bicyclic peptide inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 68 publications
1
40
0
Order By: Relevance
“…Deficient regulation of the system is exemplified by the disorder hereditary angioedema where reduction of the natural inhibitor serpin C1 or a hyperactivated FXII results in excessive bradykinin generation and recurrent attacks of severe tissue swelling . PKa is currently being targeted as a novel means to treat diverse thrombotic and inflammatory disorders such as diabetic macular edema , desquamating skin diseases, and neurodegenerative disorders .…”
Section: Introductionmentioning
confidence: 99%
“…Deficient regulation of the system is exemplified by the disorder hereditary angioedema where reduction of the natural inhibitor serpin C1 or a hyperactivated FXII results in excessive bradykinin generation and recurrent attacks of severe tissue swelling . PKa is currently being targeted as a novel means to treat diverse thrombotic and inflammatory disorders such as diabetic macular edema , desquamating skin diseases, and neurodegenerative disorders .…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical safety of bicyclic peptide was assessed upon systemic administration in rats and cynomolgus non-human primates. No overt toxicological effect observed at the highest tested systemic dose of 125 μg (0.43 − 0.60 mg/kg) in rats and 1.25 mg (0.42 − 0.49 mg/kg) in cynomolgus non-human primates [56].…”
Section: Thr-149mentioning
confidence: 89%
“…THR-149 (Oxurion NV) is a potent human plasma kallikrein bicyclic peptide inhibitor developed using a phage display-based selections of constrained peptide libraries combined with rationally designed synthetic modifications. The pharmacodynamic effect of a bicyclic peptide was assessed in a streptozotocin (STZ) induced retinal permeability in a rodent model [56]. A significant reduction in retinal vascular leakage was observed at 4 weeks, compared to the vehicle-treated group, following an intravitreal administration of a bicyclic peptide inhibitor (100 μg/eye).…”
Section: Thr-149mentioning
confidence: 99%
“…The effects of both classes on diabetic retinopathy are also very different. Some studies have suggested that plasma kallikrein contributes to retinal vascular dysfunctions in diabetic rats [13, 25] and that its inhibitors can improve diabetic macular oedema [26]. Other studies have shown that tissue kallikrein improves diabetic retinopathy by inhibiting retinal vascular permeability and VEGF increases in diabetic rats [14].…”
Section: Discussionmentioning
confidence: 99%